Scaling Up Sweetpotato through Agriculture and Nutrition in Kenya - International Potato Center (2016)
A total of 18,526 households were reached with OFSP vines and nutrition messages by August 2016. Previously non-existent in households, OFSP is being consumed at least twice a week, especially when the roots are in season. This past season, over 150 tons of roots were delivered to the puree processor, Organi Limited. This is a significant milestone considering that in 2015, the processor struggled to obtain 500 kg per day to initiate processing.